GE_GERICHTE A/2898/2020 vom 7. September 2021 - GE Cour de justice (2021)
AMENDE;SANCTION ADMINISTRATIVE;TRAVAUX DE CONSTRUCTION;GRAVITÉ DE LA FAUTE | LCI.7; RCI.10A.al1; LPAI.6.al2; LCI.137; LCI.11.al4